2014
DOI: 10.1007/s00394-014-0816-7
|View full text |Cite
|
Sign up to set email alerts
|

Short-term moderate exercise provides long-lasting protective effects against metabolic dysfunction in rats fed a high-fat diet

Abstract: Four weeks of moderate exercise at low frequency was able to prevent the metabolic changes induced by a HFD but not the deleterious effects of diet on the cardiovascular system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 61 publications
2
18
0
Order By: Relevance
“…Exercise of moderate intensity corresponded to a treadmill velocity that elicited between 55 and 65% of VO 2max and was adjusted to the value of final workload achieved in effort tests (average 50 cm/s). The intensity of the training was confirmed at 70, 85, and 98 days of life using a maximum effort test (Tofolo et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise of moderate intensity corresponded to a treadmill velocity that elicited between 55 and 65% of VO 2max and was adjusted to the value of final workload achieved in effort tests (average 50 cm/s). The intensity of the training was confirmed at 70, 85, and 98 days of life using a maximum effort test (Tofolo et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…At 30, 60, 70, 85, and 98 days of life, physical trained (Ex) animals performed an effort test to determine VO 2max utilizing a gas analyzer coupled to a hermetically sealed cage with an individual treadmill for rodents (Panlab, Harvard Apparatus®, Cornellà- Barcelona—Spain). The test began with a warm up (5 min/10 cm/s/0° of inclination), followed by increments of 9 cm/s every 3 min until exhaustion of the animal; defined as when the animal was unable to keep the pace set by the treadmill (Ferreira et al, 2007 ; Tofolo et al, 2015 ). The final workload was considered to be the velocity at which animals were exhausted and were not able to maintain their running velocity.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, Palma-Rigo and colleagues observed that physical training was unable to negate some of the harmful effects of an HFD on the cardiovascular system (27). Additionally, Canet-Soulas and colleagues reported that exercise did not protect against the side effects of high cholesterol intake on cardio-metabolic risk (28).…”
Section: Introductionmentioning
confidence: 99%
“…The findings presented by Lee et al show that MDPs play a role in whole‐body metabolic balance in mice, which highlights the importance of mitochondria not just as end‐point fat burners but also as key players in endocrine regulation. Interestingly, the protection conferred by MOTS‐c against the deleterious effects of a high‐fat diet shares many similarities with that provided by regular exercise (Tofolo et al, ). The stimuli elicited by exercise induce phenotype modifications at the skeletal muscle level that increase oxidative capacity and fat utilization while reducing lipid‐mediated insulin resistance (Samuel and Shulman, ).…”
mentioning
confidence: 97%
“…Interestingly, the protection conferred by MOTS-c against the deleterious effects of a high-fat diet shares many similarities with that provided by regular exercise (Tofolo et al, 2014). The stimuli elicited by exercise induce phenotype modifications at the skeletal muscle level that increase oxidative capacity and fat utilization while reducing lipid-mediated insulin resistance (Samuel and Shulman, 2012).…”
mentioning
confidence: 99%